Pengembangan Media Pembelajaran Persamaan Kuadrat melalui Android untuk Meningkatkan Minat Belajar Siswa - Wahyudin, Asep (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objective was to develop environmentally sensitive media through android for improving the students’ interest in learning quadratic equation. A Research and Development (R&D) with ADDIE model was designed to improve the students’ interest. Data were collected through content analysis of quadratic equation and implementation of technology-based learning procedures. The media was developed, implemented and evaluated. The media was validated by two experts on content with values of 112.7 and 120.62 respectively; validation on media with values 46.39 and 53.16 respectively; validation on technicality with values 30.2 and 30.0 respectively. The formative evaluation result shows that the students’ learning interest could be improved to a score of 76.17 with 20 point increment.